History and development of the cadaveric blood transfusion method in surgery (on the 90th anniversary of the discovery of the method) - E. Yu. Lazareva (Вестник хирургии имени И.И. Грекова)
The article is devoted to the development and implementation of the method of hemotransfusion of cadaveric blood to living people, thanks to which methods of blood preservation, fibrinolysis received its development. Currently, this method of hemotransfusion therapy may be in demand in the use of components of donor blood, including, from a conditioned donor, in organ transplantation to single-group recipients. Understanding the process of fibrinolysis is key to preventing and stopping bleeding in certain surgical pathologies.